Proses Pemindahan Lokasi Penimbunan Kontainer Impor di Depo PT. Karana Panorama Logistik Surabaya - Ardyka Putra, Eka Yudha; Nugroho, F. X. Adi Purwanto; Pradana Putra, Revian Nico (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2023)
PT. Karana Panorama Logistics Surabaya is a company engaged in providing land for the stacking of both empty and full containers. In the activities that exist in PT. Karana Panorama Logistics Surabaya, one of which is to reduce the high number of dwelling time at the port by providing a place to move the location of the imported container stockpiling. The purpose of this research is to find out how the process of moving the landfill site occurs and also what are the criteria for providing a landfill location. In this study, researchers used qualitative research methods to determine the strengths, weaknesses, opportunities and threats for the company. From the problems found, the researchers found the cause of the transfer of the location of the hoarding and how the process was carried out before the transfer of goods occurred from TPS Line I to TPS Line II. The results of the study can be concluded that the implementation of the long stay of goods in the port area is intended to reduce dwelling time and create activities for relocating this stockpiling location.